1996
DOI: 10.1063/1.116554
|View full text |Cite
|
Sign up to set email alerts
|

Blue luminescence from Si+-implanted SiO2 films thermally grown on crystalline silicon

Abstract: From fabrication to mode mapping in silicon nitride microdisks with embedded colloidal quantum dots Appl. Phys. Lett. 101, 161101 (2012) Vanadium bound exciton luminescence in 6H-SiC Appl. Phys. Lett. 101, 151903 (2012) Broadband near-infrared emission from bismuth-doped multilayer films J. Appl. Phys. 112, 073511 (2012) Enhancement of carbon nanotube photoluminescence by photonic crystal nanocavities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(114 citation statements)
references
References 16 publications
8
105
1
Order By: Relevance
“…Blue luminescence was also observed in Si + -implanted SiO 2 films peaking at around 2.7 eV, which was believed to be due to oxygen vavancy. 61 It is therefore reasonable for us to believe that the very intensive blue light emission from the SiO 2 nanotubes can be attributed to the abovementioned defect centers arising from the oxygen deficiency.…”
Section: Cathodoluminescence (Cl)mentioning
confidence: 99%
“…Blue luminescence was also observed in Si + -implanted SiO 2 films peaking at around 2.7 eV, which was believed to be due to oxygen vavancy. 61 It is therefore reasonable for us to believe that the very intensive blue light emission from the SiO 2 nanotubes can be attributed to the abovementioned defect centers arising from the oxygen deficiency.…”
Section: Cathodoluminescence (Cl)mentioning
confidence: 99%
“…7 Zacharias and Fauchet 3 argued that ∼400 nm blue luminescence must be related to the formation of Ge or GeO 2 nanocrystals in the oxide matrix and they suggested that defects at the NC/matrix interface is responsible for the emission. On the other hand, Liao et al 8 and Feinardi and Paleari 9 observed violet PL in SiO 2 samples that does not contain Ge atoms and the violet emission was attributed to oxygen deficient defects in SiO 2 . Violet luminescence in Ge nanocrystals/Ge oxide structures formed by dry oxidation of polycrystalline SiGe has been attributed to defects at the NC Ge/GeO 2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous silica as an important optical candidate material has been investigated for a long time, due to its unique physical and chemical stability and efficient photoluminescence emission [1]. Especially one dimensional silica materials, such as tubes [2], rods [3], wires [4], and fibers [5] have attracted a lot of attentions during the past decades because of their potential wide-ranging applications, for example drug delivery [6], catalysis [7], controlled release [8] and biological filed [9].…”
Section: Introductionmentioning
confidence: 99%